2016
DOI: 10.1038/srep31434
|View full text |Cite
|
Sign up to set email alerts
|

Neutrons describe ectoine effects on water H-bonding and hydration around a soluble protein and a cell membrane

Abstract: Understanding adaptation to extreme environments remains a challenge of high biotechnological potential for fundamental molecular biology. The cytosol of many microorganisms, isolated from saline environments, reversibly accumulates molar concentrations of the osmolyte ectoine to counterbalance fluctuating external salt concentrations. Although they have been studied extensively by thermodynamic and spectroscopic methods, direct experimental structural data have, so far, been lacking on ectoine-water-protein i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
56
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 69 publications
(59 citation statements)
references
References 63 publications
1
56
0
2
Order By: Relevance
“…36 Ectoine is known to be expelled from the first hydration shell of charged surfaces and biomolecules. 6,7,11 However, its presence in solution will inevitably decrease the amount of water around DNA in the biologically relevant target volume of 10-15 nm diameter. 20,37 Therefore, ectoine may act as a protective agent by passively displacing water from the surroundings of the DNA.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…36 Ectoine is known to be expelled from the first hydration shell of charged surfaces and biomolecules. 6,7,11 However, its presence in solution will inevitably decrease the amount of water around DNA in the biologically relevant target volume of 10-15 nm diameter. 20,37 Therefore, ectoine may act as a protective agent by passively displacing water from the surroundings of the DNA.…”
Section: Discussionmentioning
confidence: 99%
“…3) in the solid 4 state and in water, 5 exerts a kosmotropic effect on the local water structure [5][6][7][8] as well as an influence on protein functions. 7,[9][10][11] Moreover, various studies [12][13][14] investigated the effects of ectoine on biological damage caused by ultraviolet radiation (UV) of various wavelengths. The study by Bünger et al 13 found that UV-A (340-400 nm) irradiated human keratinocytes show a decrease in mitochondrial DNA mutations for cells pretreated with ectoine.…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, this amino acid derivative does not interact directly with protein surfaces but rather it forms a molecular net holding water molecules close to the macromolecule (10,18,19). Moreover, Roychoudhury et al (20) have shown that ectoine, like other compatible solutes, strengthens intramolecular interactions essential for protein stability.…”
Section: Stabilising Enzyme Activitymentioning
confidence: 99%
“…Harishchandra et al (28) propose that ectoine increases cell membrane fluidity to cope with extreme conditions such as high temperature or osmotic pressure. A recent biophysical study by Zacchai et al (10) showed that ectoine is excluded from the hydration layer at the membrane surface and does not affect membrane molecular dynamics. Moreover, improved hydration of the cell surface thanks to ectoine increases intermolecular spacing and boosts the mobility of the lipid head groups in the cell membrane ( Figure 2) (29).…”
Section: Cell Protectionmentioning
confidence: 99%
See 1 more Smart Citation